2009
DOI: 10.1002/cjas.105
|View full text |Cite
|
Sign up to set email alerts
|

Diversity management versus gender equality: the finnish case

Abstract: The notion of diversity management (DM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 53 publications
0
49
1
5
Order By: Relevance
“…First emerging in the USA, it is increasingly implemented in Europe, where it first entered the policy field in the late 1990s (Gordon 1995;Lorbiecki and Jack 2000;Vertovec and Wessendorf 2010;Neuhold and Scheibelhofer 2010). Single and comparative case-studies of diversity management in different national contexts show that diversity (management) takes on different meanings in relation to national migration histories and policies as well as equality legislation (Greene, Kirton and Wrench 2005;Kalonaityte 2009;Meriläinen et al 2009;Sénac and Forest 2015;cf. Pécoud 2015, 38-39 on the difficult translatability of migration management).…”
Section: Migration Management and Diversity Managementmentioning
confidence: 99%
“…First emerging in the USA, it is increasingly implemented in Europe, where it first entered the policy field in the late 1990s (Gordon 1995;Lorbiecki and Jack 2000;Vertovec and Wessendorf 2010;Neuhold and Scheibelhofer 2010). Single and comparative case-studies of diversity management in different national contexts show that diversity (management) takes on different meanings in relation to national migration histories and policies as well as equality legislation (Greene, Kirton and Wrench 2005;Kalonaityte 2009;Meriläinen et al 2009;Sénac and Forest 2015;cf. Pécoud 2015, 38-39 on the difficult translatability of migration management).…”
Section: Migration Management and Diversity Managementmentioning
confidence: 99%
“…The managers framed the lack of ethnic minorities in the managerial ranks primarily in terms of lack of qualifications. In contrast to the prevailing notion that minorities lack the necessary education to be managers, the underrepresentation of managerial women has often been framed in essentialist terms based on assumptions about women's reproductive capabilities and responsibilities as primary caregivers and has often been confounded with sexual preference and heteronormativity (Wajcman 1998, Claringbould and Knoppers, 2004, 2008, Connell 2006, Meriläinen et al 2009, Knoppers et al 2012. For example, Claringbould and Knoppers (2004) found in a study of practices among senior sport journalists that the underrepresentation of women was attributed to the 'natural' care-giving abilities and responsibilities of married heterosexual women.…”
Section: Managerial Practices Of Diversity and Homogeneitymentioning
confidence: 99%
“…(Edelman et al 2001(Edelman et al , p. 1631. Senior managers create homogeneity or diversity by legitimating or reframing hierarchies embedded in dominant organizational and societal discursive practices (Meriläinen et al 2009). For example, research in academia has shown that decisions about criteria for promotion, although seemingly gender-neutral and meritocratic, tend to favor men (Benschop and Brouns 2003, Van den Brink and Benschop 2012, Fotaki 2013.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an approach holds that DM is "good for business" as well as "important in its own right" (Olsen andMartins, 2012, p. 1171). In parallel, researchers have investigated corporate websites in order to find if the content of their organizational mission statements and other reports someway incorporate diversity concerns (e.g., Guerrier and Wilson, 2011;Heres and Benschop, 2010;Meriläinen et al, 2009;Point and Singh, 2003;Singh and Point, 2004;Wallace et al, 2014) or discourses of diversity (Zanoni and Janssens, 2015). Overall, it is assumed that the documents aforementioned depict a coherent organizational discourse toward diversity and related issues, given the growing relevance of this topic.…”
Section: Introductionmentioning
confidence: 99%